Integration of storage and renewable energy into district heating systems: a review of modelling and optimization - Olsthoorn, Dave; Haghighat, Fariborz; Mirzaei, Parham A. (Elsevier, 2016)
The building and infrastructure sector is accountable for 46% of the total worldwide energy consumption. Most traditional energy sources such as coal or petroleum are among the non-renewable types and most likely to be depleted in the forthcoming decades. To address the current energy crisis, use of renewable energy such as solar sources and a considerable increase in energy efficiency are proposed as the potential solutions. District heating systems (DHS), in particular, has recently received more attention due to several advantages in energy production, distribution and consumption for the space heating.